2012
DOI: 10.1016/j.neuroscience.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise is the critical variable in an enriched environment that increases hippocampal neurogenesis and water maze learning in male C57BL/6J mice

Abstract: Previous studies have shown that housing mice with toys and running wheels increases adult hippocampal neurogenesis and enhances performance on the water maze. However, the relative contribution of running versus enrichment to the neurogenic and pro-cognitive effects is not clear. Recently, it was demonstrated that enrichment devoid of running wheels does not significantly enhance adult hippocampal neurogenesis in female C57BL/6J mice. However, novel toys were not rotated into the cages, and dietary enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 42 publications
(67 reference statements)
12
109
2
3
Order By: Relevance
“…At a behavioural level, improvements in spatial learning and memory, associative learning and recognition memory have all been observed in animals following exercise training. Mice housed with a running wheel perform better in the MWM compared to their sedentary counterparts (Clark et al, 2008;Gibbons et al, 2014;Mustroph et al, 2012), while exercising mice also outperformed their sedentary counterparts in the contextual fear conditioning task (Bhattacharya et al, 2015;Clark et al, 2008;Gibbons et al, 2014). Data from our laboratory has demonstrated that rats trained on a treadmill perform better than their sedentary counterparts in the novel object recognition and object displacement tasks of recognition and spatial memory respectively (Griffin et al, 2009).…”
Section: Adult Hippocampal Neurogenesis and Exercisementioning
confidence: 97%
“…At a behavioural level, improvements in spatial learning and memory, associative learning and recognition memory have all been observed in animals following exercise training. Mice housed with a running wheel perform better in the MWM compared to their sedentary counterparts (Clark et al, 2008;Gibbons et al, 2014;Mustroph et al, 2012), while exercising mice also outperformed their sedentary counterparts in the contextual fear conditioning task (Bhattacharya et al, 2015;Clark et al, 2008;Gibbons et al, 2014). Data from our laboratory has demonstrated that rats trained on a treadmill perform better than their sedentary counterparts in the novel object recognition and object displacement tasks of recognition and spatial memory respectively (Griffin et al, 2009).…”
Section: Adult Hippocampal Neurogenesis and Exercisementioning
confidence: 97%
“…If a mouse didn't reach the platform in 60 s, it meant that its escape latency was 60 s, then the mouse was allowed to rest for 30 s between trials. On the fifth day, the platform was removed and mice were tasked with a probe trial for 2 min [31,32].…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…ответе на возбуждение у животных при столкновении с новыми объектами [14] Теория обучения Посредником морфологических изменений являются клеточные механизмы, лежащие в основе процессов обучения [10] выживаемость нейронов у мышей [15]. Интересно, что ОС, не подразумевающая высокой моторной активно-сти, лишь незначительно стимулирует гиппокампальный нейрогенез [31], тогда как применение беговых колес способствует более интенсивной пролиферации клеток в зубчатой извилине у мышей, содержащихся в условиях социальной и физической депривации, по сравнению с мышами, содержащимися в условиях ОС [32]. Таким об-разом, факторы ОС, вероятнее всего, избирательно дей-ствуют на разные компоненты программы нейрогенеза, а также дополнительно дифференцированно стимулиру-ют глио-, синапто-и ангиогенез, как это было предло-жено W. Greenough и соавт.…”
Section: нейрогенез и нейрон-глиальные взаимоотношения в условиях обоunclassified